IMPLEMENTASI KEBIJAKAN PENYEDIAAN AIR BERSIH DI KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Vivin Delvya Roza; Sujianto Sujianto (Cross-border, 2023)
Provison of clean water needs it the responsibility of the central or regional government which must be met by the community. The purpose or this study is to analyze and describe how the implementation of the clean water supply policy in Inuman District and find out what are the inhibiting factors in its implementation as seen from standard indicatrs and policy objectives, resources, inter-organizational relations, characteristics of implementing agents, social environment, economy, politics and the dispisition of the implementer. This study uses a qualitative method with a descriptive approach. The results of this study indicate that the implementation of clean water supply policies in Inuman Districts has not run optimally, has not been able to eet policy standards, espencially in terms of quantity, quality and continuity of water. Likewise with the policy target, it is found that many people in Inuman District have not had access to clean wter from PAB. The existence of limited human resources in terms of number and expertise is indicated by the many complaints from the community regarding the length of the repair process if damage occurs the limited financial resources and lack of infrastructure in distributing clean water. Coordination between policy implementing agencies through face-to-face meetings and communication through the network has been carried out but the frequency of meetings is not fixed so that effective communicatin has not been seen. In the social environment there are still many people who cannot be served by PAB, in an econimic environment low tariffs prevent PAB from investing in clean water supply and support from political actors helps achieve policy goals. The attitude of the executor is disiplined towards directions but the absence of incentives affects employee morale, then it has inhibiting factors, namely the lack of budget and human resources and the poor quality of raw water.